PENINGKATAN DAYA SAING TENAGA KERJA DOMESTIK MELALUI PELATIHAN KETERAMPILAN PADA DINAS TENAGA KERJA DAN TRANSMIGRASI PROVINSI RIAU - Suharman, Fachrul Sidiq; Pabisa, Djonny (Institut Pemerintahan Dalam Negeri, 2023)
The Provincial Department of Manpower and Transmigration of Riau plays an important role in enhancing the competitiveness of domestic workers to overcome unemployment resulting from the COVID-19 pandemic. One of the strategies used is through skill training programs conducted at the Training and Job Placement Center. The Quality and Productivity Improvement Program for Workers is implemented to enhance the competence and productivity of workers in Riau Province. Therefore, this study aims to evaluate the effectiveness of the skill training program conducted by the Provincial Department of Manpower and Transmigration of Riau in improving the competence and productivity of workers in the province. The study uses a qualitative research design with an inductive approach. Data collection techniques include observation, interviews, and documentation. Data analysis techniques used include data reduction, data presentation, verification, and conclusion drawing. The study uses the concept of competitiveness by Pratiwi and Mahmudah in Ibnu Khaldun, 2020, which consists of 5 dimensions including Health, Education, Technology, Communication, and Skills. The results of the study indicate that despite the efforts made, there are constraints in the Health dimension, such as incomplete health facilities, in the Education dimension, there is a shortage of instructors, in the Skills dimension, there is a general curriculum, in the Communication dimension, the implementation of foreign language training is not routine, and in the Technology dimension, some participants are not accustomed to using the latest equipment. Other inhibiting factors include a shortage of instructors, stagnant competency development, lack of understanding by potential participants, and a lack of understanding by participants about technology. Efforts made to overcome these barriers include handing over the management of the Training and Job Placement Center to the Central Government, increasing the Apprenticeship Program, and collaborating with private sector institutions. Suggestions to improve the program include re-allocating the skill training budget to meet the needs of facilities and infrastructure, planning additional foreign language training, recruiting experienced instructors, and increasing the socialization of skill training programs through social media, especially for vocational school students and young job seekers.